Analisis Kausalitas antara Sektor Keuangan dan Pertumbuhan Ekonomi di Indonesia - Maski, Ghozali (Jurnal Ekonomi dan Pembangunan Indonesia, 2010)
The economic growth of the country is inseparable from the development of its financial sector. Therefore, this research attempted to prove the existence of causality between financial sector and economic growth in Indonesia using data between Ql of 1996 to Q4 of 2006. The variables used as proxy for financial sector are monetization, private credit, total deposits, stock market capitalism, and stock market value traded-while the real GDP is used as a proxy for economic growth. This research aims to determine which variable is the most dominant influence in the shock given in causality result.This research methodology used Vector Error Correction Model (VECM) and Granger causality. VECM is used to find out the dominant variable that gave shock, while Granger causality is used to detect the causality between variables. Granger causality test shows the existence of one way causality between real GDP and private credit, total deposit, and stock market value traded. These causalities come from three sources. First, from real GDP to private credit; second, from real GDP to stock market value traded; and the last, from total deposit to real GDP. Meanwhile, VECM test shows the result that the economic growth can be a boosting factor for Indonesian financial sector growth. Moreover, the dominant variable in creating shock on economic growth is stock market value traded. The Granger causality estimation shows that there are one-way causalities between real GDP and private credit, total deposit, and stock market value traded.